Transforming Global Citizenship: A Narrative Study of IISMA Students' Experiences in the International Arena - Indah, Dwi Filadelfia; Hida, Yinarti (Jambura Journal Civic Education, 2025)
This study aims to analyse the transformation of global citizenship through the experiences of Indonesian students in the Indonesian International Student Mobility Awards (IISMA) programme, focusing on the practice of cultural diplomacy and advocacy of global issues. This study examines how students who participate in international mobility programmes build intercultural competence, strengthen national identity, and develop critical awareness of global issues such as climate justice, human rights, and decolonisation of knowledge. Using a qualitative approach with a narrative study design, data were collected through in-depth interviews with IISMA participants from two universities in Indonesia and a reflective analysis of their experiences during the programme in various countries. Thematic analysis was conducted by referring to the theories of global citizenship, epistemic agency, and soft power. The results of the study show that international experience plays an important role in the formation of students' global citizenship identity, both through cultural diplomacy in cross-cultural interactions and active participation in global discourses. Students transform into cultural and knowledge agents who bridge local and global perspectives. These findings emphasise the urgency of integrating intercultural literacy, critical reflection, and global ethics in international mobility programmes to strengthen the role of higher education in producing inclusive and transformative world citizens.